THEORETICAL FOUNDATIONS OF DEVELOPING PROFESSIONAL AND COMMUNICATIVE COMPETENCE IN AVIATION EDUCATION (Web of Teachers: Inderscience Research, 2026)
This article explores the theoretical foundations of developing professional and communicative competence in aviation education. In the context of globalization and increasing international cooperation in the aviation industry, effective communication skills have become a crucial component of professional training for aviation specialists. The study examines the concept of professional-communicative competence as an integrated system that includes linguistic, sociocultural, and professional components necessary for safe and efficient communication in aviation environments. Particular attention is given to the role of foreign language teaching, especially English as the language of international aviation, in shaping communicative competence among future aviation professionals. The article analyzes modern pedagogical approaches, including communicative and competence-based methods, which contribute to the development of students’ practical communication skills. Furthermore, the research highlights the importance of integrating theoretical knowledge with real-life communicative situations, such as pilot-controller interaction and aviation-specific discourse.